The Effect of Digital Learning Media Usage on Digital Economic Literacy with Self-Efficacy as an Intervening Variable among Students of SMA Negeri 62 Jakarta - Hayati, Innisa Kumala; Suparno, Suparno; Pratama, Aditya (The Future of Education Journal, 2025)
This study aim for know influence use of digital learning media towards literacy digital economy with self-efficacy as intervening variables in students State Senior High School 62 Jakarta . Research This For know influence direct and indirect direct . Research This use method quantitative with method data collection using questionnaire . Number the sample was 169 students from population used​ student Class X. Data analysis using SEM-PLS with SmartPLS software . Research results this , influence direct use of digital learning media towards literacy student digital economy with the path coefficient showing original sample value 0.399 > 0, t- statistic 5.868 > 1.96 and p-value 0.000 < 0.05, the influence direct limited use of digital learning media self-efficacy student with the path coefficient showing original sample value 0.660 > 0, t- statistic 12.792 > 1.96 and p-value 0.000 < 0.05, the influence direct self-efficacy student to literacy student digital economy with the path coefficient showing original sample value 0.497 > 0, t- statistic 6.935 > 1.96 and p-value 0.000 < 0.05. And the influence No direct use of digital learning media towards literacy digital economy through self-efficacy with the path coefficient showing original sample value 0.328 > 0, t- statistic 6.421 > 1.96 and p-value 0.000 < 0.05.